PENGARUH SISTEM PENTANAHAN TERHADAP ARUS GANGGUAN TANAH PADA SISTEM DISTRIBUSI 20 KV - Muhammad Sidik Kalosa; sabar setiawidayat; mohammad mukhsim (PTE FTK UIN Ar-Raniry, 2020)
The process of electricity distribution often have been affected , including disruption to the ground. This study aims to analyse the impact of the current Ground system disorder to land at kV 20 distribution systems. Ground system that is solid analysis system , resistor , reactor. In a comparison with looked at and charts using etap 12.6. With the Ground solid System on a bus 2 with distance 300 m of the disorder of plants having 30.066. kA. For the current disorder 2 the phase to the ground having the disruption of 30.903 kA by the distance where closer the disorder bigger the disorder land so does the contrary